Modeling and Simulation of Composite Materials for SLS-Based 3D Printing - Ali, Hazrat; Yerbolat, Gaziz; Abilgaziyev, Anuar (Manufacturing Technology Journal, 2020)
This paper discusses the modeling and simulation results of a new multi-material for a cost-effective Selective Laser Sintering (SLS)-based 3D printer. As this technology utilizes several materials, the me-chanical property analysis of multi-materials is crucial for manufacturing an object with the desired physical characteristics. Firstly, the development of a database of the SLS 3D printing materials is ac-complished and based on the mechanical properties of materials, this optimization technique is proposed. Secondly, enhancement of physical property by stiffeners is considered and based on the stiffening tech-nology, and an alternative optimization method proposed. Finally, two different material minimization methods are discussed in this research. The first method is based on the embedded materials with desired mechanical properties for enhancing the mechanical properties of the printed objects, which are twice optimized by this method with increased material saving. The second method is designed to use stiffeners to improve the stiffness characteristics of the materials, and then, perform material optimization. This method is effective with more suitability to complex composite geometries. Thus, the methods help to reduce materials used as well as the production cost in 3D printing technology.
Keywords: Additive Manufacturing; 3D Printing; Composite Materials; Material Properties